Investigating Drama in Teaching Practice - Seniarika Seniarika (Edukasi Lingua Sastra, 2017)
Drama is widely used in English class inasmuch as drama is considered as a way to learn English effectively. A lot of researcher conducted studies on drama either aimed to find out the benefits obtained through drama or aimed to find out the difficulties that might be found by the learners in drama. This article reviews five articles in relation with drama. The researcher in those studies investigated drama from different perspective. The result found in this study is expected to be consideration in implementing drama in teaching practice.